Estimation of enteric methane emissions in dairy cows under grazing a silvopastoral system and a grass monoculture in the Colombian Amazonian foothills - Juan Pablo Narváez-Herrera; Joaquín Angulo-Arizala; Wilson Andrés Barragán-Hernández; Liliana Mahecha-Ledesma (PLoS ONE, 2026)
Mitigating enteric methane in the humid tropics, particularly in the Colombian Amazonian foothills, remains challenging due to limited field-based data under real grazing conditions. This study evaluated the performance of a laser methane detector (LMD) as a non-invasive alternative to traditional techniques, providing the first field-based validation of this approach in Amazonian grazing systems. Two contrasting production systems were compared: a silvopastoral system (SPS) with trees and shrubs, and a grass monoculture (traditional pasture, TP). A crossover design (two groups of five cows) was implemented across four periods. The LMD enabled repeated, activity measurements without disrupting natural behavior, capturing emissions during grazing, ruminating, resting, and milking. Daily CH₄ emissions were significantly lower in SPS than TP (233 ± 6.95 vs. 277 ± 8.87 g CH₄ animal ⁻ ¹ day ⁻ ¹; p < 0.0001). Methane intensity also decreased in SPS when expressed per kg milk (15.5 vs. 20.7 g CH₄ kg ⁻ ¹), energy-corrected milk (16.0 vs. 21.2 g CH₄ kg ⁻ ¹), and dry matter intake (18.9 vs. 26.7 g CH₄ kg DMI ⁻ ¹; all p < 0.0001). Classification was based on animal activity rather than diet, allowing detailed behavioral associations with CH₄ release dynamics. While the LMD requires strict environmental protocols and does not capture continuous 24-h data, its portability and non-invasive nature make it a practical, scalable tool for tropical field conditions. These results provide novel evidence supporting SPS as a mitigation strategy, strengthen GHG inventories in tropical livestock systems, and offer guidance for policymakers promoting sustainable production systems.